Evaluation of antibacterial preparations on growth rate and feed efficiency of young pigs - G L Allee; B A Koch; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1976)
Ninety-six young pigs were used to evaluate various antibacterial preparations on rate and efficiency of gain. Each of the antibacterial preparations increased rate of gain over pigs fed the non-medicated basal diet. There were no significant differences in daily gains of pigs fed ASP-250, CSP-250, Lincomix, Mecadox, or Stafac.; Swine Day, Manhattan, KS, November 11, 1976
Keywords: Swine day; 1976; Kansas Agricultural Experiment Station contribution; no. 519-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 283; Swine; Antibacterial preparations; Growth rate; Feed efficiency; Daily gain